2018
DOI: 10.1002/hon.2563
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of baseline 18FFDG PET/CT parameters in MALT lymphoma

Abstract: Mucosa‐associated lymphoid tissue (MALT) lymphoma is an indolent lymphoma with good prognosis and variable fluorine‐18 fluorodeoxyglucose (18F‐FDG) avidity. Many possible prognostic factors have been investigated with controversial results, but the possible prognostic role of 18F‐FDG positron emission tomography/computed tomography (PET/CT) remains unclear. Our aim was to evaluate the prognostic impact of qualitative and semiquantitative baseline PET/CT parameters on outcome of MALT lymphoma. We retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…This is in accordance with a recent retrospective analysis of 161 PET/CT − BMB− 19 (26) patients with MALT lymphoma, of whom 98 had positive FDG uptake, which demonstrated that baseline positive FDG uptake was not associated with PFS or OS. 25 Determining BMI may have an effect on prognosis of MZL patients because it may influence both stage and extranodal involvement, both comprising the IPI. The reported incidence of BMI in SMZL is 70% to 100%, and for the other subtypes of MZL, 30% to 40%.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with a recent retrospective analysis of 161 PET/CT − BMB− 19 (26) patients with MALT lymphoma, of whom 98 had positive FDG uptake, which demonstrated that baseline positive FDG uptake was not associated with PFS or OS. 25 Determining BMI may have an effect on prognosis of MZL patients because it may influence both stage and extranodal involvement, both comprising the IPI. The reported incidence of BMI in SMZL is 70% to 100%, and for the other subtypes of MZL, 30% to 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other PET parameters related to the metabolic volumes (MTV and TLG) were derived and were defined as parameters that represent the morphological and metabolic features in the same feature [37]. In the literature, other manuscripts investigated the potential role of MTV and TLG in lymphoproliferative diseases, especially in the prognostic field [38][39][40][41], but in CLL patients only two studies [23,26] analyzed these factors, reporting controversial results. For Pontoizeau et al [23], baseline MTV was a predictor of overall survival in RT, while in the other paper [26], MTV and TLG were not related to survival.…”
Section: Discussionmentioning
confidence: 99%
“…DS and SUVmax were not centrally determined, although the PET/CT image was reviewed by experienced physicians at each institution. The SUV reliability can be influenced by many factors such as blood glucose level, technological characteristics, partial volume effect, injected dose and decay of radiotracer 31 . However, recent studies suggest that PET/CT response assessments using DS have small interobserver differences 32,33 .…”
Section: Discussionmentioning
confidence: 99%